عقد المضاربة في التأمين الشرعي من منظور الفقه الإسلامي والقانون الاندنوسية: دراسة فقهية قانونية مقارنة: Mudarabah Contract in Islamic Insurance: A Comparative Study of Islamic Jurisprudence and Indonesian Law - Yudhatama, Muhammad Zacky; Abdul Hadi, Ahmad (Universitas Muhammadiyah Surakarta, 2026)
This study examines the Mudarabah contract as a key Sharia-based investment tool and assesses its suitability as a contractual model for Islamic insurance (ta’min shar‘i). It aims to offer a Sharia-compliant alternative to conventional insurance, which often entails prohibited elements such as gharar (excessive uncertainty), riba (usury), and maysir (gambling). The research investigates the foundational principles, pillars, and conditions of the Mudarabah contract, exploring how it can be adapted to align with the characteristics of Islamic insurance contracts. Additionally, a comparative analysis is conducted between Islamic jurisprudence and positive law governing Islamic insurance, focusing on fund management, profit and loss distribution, and contractual obligations. Findings show that the Mudarabah contract can promote contractual fairness and enhance trust between parties if Sharia principles are consistently observed. There is partial alignment between provisions of Islamic jurisprudence and positive law; however, legislative reforms are needed for complete harmony with Sharia. The model supports the maqasid al-shariah objectives, including the protection of wealth, justice, and the prevention of harm. It addresses critical issues such as participant fund management, profit-loss sharing, and enforcement of contractual rights. This research contributes significantly to the literature on Sharia-based investment contracts and opens opportunities to develop diverse, competitive, and ethically sound Islamic insurance products. By integrating Islamic jurisprudential insights with contemporary legal frameworks and market demands, the Mudarabah contract can serve as an effective contractual model that meets Sharia requirements while adapting to the modern financial industry.